Sodium-assisted passivation of grain boundaries and defects in Cu2ZnSnSe4 thin films. Issue 14 (30th March 2020) - Kim, Juran; Kim, Gee Yeong; Nguyen, Trang Thi Thu; Yoon, Seokhyun; Kim, Yoon-Koo; Lee, Seung-Yong; Kim, Miyoung; Cho, Dae-Hyung; Chung, Yong-Duck; Lee, Je-Ho; Seong, Maeng-Je; Jo, William
Abstract : CZTSe thin-films are deposited on Mo-coated soda-lime glass (SLG) and Mo-coated borosilicate with and without a NaF layer. Na-doping inhibits the formation of the secondary phases and passivates the grain-boundaries (GBs). Abstract : The long stagnation of the photo-conversion efficiency of kesterites below 13% is a source of frustration in the scientific community. In this study, we investigated the effects of sodium on the passivation of grain boundaries and defects in Cu2 ZnSnSe4 (CZTSe) grown on a soda-lime glass (SLG) and borosilicate (BS) glass. Because BS glass does not inherently contain sodium, we placed a thin layer of NaF between CZTSe and Mo. The composition of the samples is Cu-poor and Zn-rich. The distribution of sodium and its contributions to phase formation and defects were examined by cross-sectional energy-dispersive X-ray profiling, Raman scattering spectroscopy and imaging, surface potential and photoluminescence. From the experimental results, it can be strongly claimed that sodium ions segregate predominantly near the grain boundaries and reduce CuZn -related defects. These local surface imaging analyses provided the exact locations of the secondary phases. In particular, the photo-assisted scanning probe method enabled us to observe the changes in the optoelectrical properties of the thin films and the carrier behavior within the materials. Further studies with distinct alkali ions and optimal processing conditions will pave a way to improve the performance of kesterite solar cells.